Maternity services' responses to the COVID-19 pandemic: how Public Health England guidance was implemented in practice. (November 2022) - Hanley, S.; Raybould, G.; Baxter, E.; Gray, J.; Sharkey, D.; Walker, K.F.
Summary: Introduction: The rapidly evolving COVID-19 pandemic required systemic change in how healthcare was delivered to minimize virus transmission whilst maintaining safe service delivery. Deemed at 'moderate-high risk', maternity patients are an important patient group that require consideration. Public Health England (PHE) issued national guidance on how to adjust these services. Aim: To explore how maternity units in England implemented PHE guidance. Methods: An online survey of 22 items was distributed to individuals that had worked on an England-based maternity unit during the COVID-19 pandemic. The questionnaire was designed and tested by the multidisciplinary research team. Data was collected from November 2020 to July 2021. Findings: Forty-four participants across 33 maternity units responded. Ninety-three percent were able to test all women requiring an overnight stay for COVID-19. Only 27% reported birth partners were tested for COVID-19. Only 73% reported they were able to isolate all COVID-19-positive patients in single rooms. Eighty-four percent stated they were aware of current PHE guidance on personal protective equipment (PPE) and 82% felt 'confident' in donning/doffing of PPE. Priorities for the future include rapid testing and a focus on community service provision. Conclusions: PHE COVID-19 guidance was implemented differently in maternity units across England due to the varying resources available at each trust leading to variable ability to test and isolate patients as recommended. More specific, tailored guidance for infection control measures against COVID-19 is needed for maternity settings due to their unique position.